Individuazione: concetto, colpa, mito - Salza, Fulvio (Filosofia, 2015)
The research of C. G. Jung revolves around the word “individuation”. On the one hand, Jung attempts at providing a rigorous definition of this concept, while on the other hand he describes it in symbolical and mythological terms. The paper aims at a thorough examination of both these aspects and at analyzing the implications of this ambivalence.